2005
DOI: 10.1111/j.1540-8159.2005.50026.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Postural Orthostatic Tachycardia Syndrome

Abstract: In long-term follow-up, both women reported improvement in their prepartum symptoms. We describe the first report, to our knowledge, of two successful pregnancy outcomes in severe POTS, including the first report of midodrine use in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 9 publications
0
40
0
3
Order By: Relevance
“…7,8 Fluid preloading has been used before establishing the block. Our patient had no obvious contraindication to regional anaesthesia, but Ehlers-Danlos syndrome may be associated with bleeding disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Fluid preloading has been used before establishing the block. Our patient had no obvious contraindication to regional anaesthesia, but Ehlers-Danlos syndrome may be associated with bleeding disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Four cases of pregnancy in women with POTS have been described. [6][7][8] In all cases epidural analgesia or anaesthesia was used but full details of anaesthetic management are available in only two of the cases. To our knowledge there is no previous report of anaesthetic management for delivery in hypermobility type Ehlers-Danlos syndrome associated with POTS.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise training and re-conditioning is emerging as a very important strategy. In a study by Glatter et al 7 lifting the baby and caring for the infant forced women to develop their upper body strength that attributed to the improvement in symptoms as well as a positive psychological outlook at six months postpartum. Treatments must be carefully tested due to medication sensitivity often associated with POTS patients, and each patient will respond to different therapies in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Beta blockers are used to treat adrenergic symptoms. 5 Glatter et al 7 was the first to describe the use of midodrine, a category C drug, in pregnancy in his patients. A study by Powless et al showed that the patients who did not require treatment for POTS prior to conception remained so with a less likely chance of exacerbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation